AB0773 Delays in recognition of giant cell arteritis presenting as fever of unknown origin: Evaluation of a hospital-based population. (23rd January 2014) - Talarico, R.; d'Ascanio, A.; Stagnaro, C.; Ferrari, C.; Bombardieri, S.
Abstract : Background: Giant cell arteritis (GCA) represents the most common primary vasculitis of the elderly, that usually involves large and medium sized arteries. The wide spectrum of clinical manifestations can extensively vary, from cranial symptoms, such as headache, jaw claudication or visual alterations, to constitutional symptoms, like fever, weight loss or asthenia. Fever of unknown origin (FUO) may sometimes represents the initial symptom of GCA and when it is not associated with other typical GCA features, the diagnosis can be unluckily delayed. Objectives: The primary aim of the study was to identify delays in recognizing patients with GCA presenting as FUO. The secondary aim was to compare the subset of GCA patients characterised by the presence of FUO at the onset, with the other cases who experienced signs and symptoms typically suggestive of GCA at the onset. Methods: Epidemiological and clinical data of 180 GCA patients followed in the last 15 years in our Unit were analysed. We quantify the latency period between the onset of signs and symptoms and the final diagnosis of GCA in terms of months. Results: One hundred and thirty-five patients (13 males and 122 females, mean ± SD age at the onset 75±6 years, mean follow-up 8 years)had shown at the onset signs and symptoms suggestive of GCA (new onset headache and/or scalp pain 78%, jaw claudication 36%, vision loss 33%, abnormal temporal artery on examination 32%, dizziness 29%) while 45 patients (9 males and 36 females, mean age at the onset 67±2 years, mean follow-up 6 years) were sent to our attention just for the onset of FUO and for an increase of erythrocyte sedimentation rate and C-reactive protein not otherwise justified. After an extensive work-up aimed at excluding any kind of infection, malignancy or hematological disorder, we performed in all patients presenting as FUO a temporal artery biopsy (TAB), that resulted positive in 52% of cases. Moreover, (18)F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) was performed in 29 cases and resulted positive in 27. The main PET alterations reported were characterized by a (18)FDG uptake of the aortic arch and its major braches, including the carotid, subclavian, thoracic aorta and, less frequently, the abdominal aorta. The mean latency period between the onset of FUO and the diagnosis of GCA was 7±2 months, that was significantly higher compared with the mean latency period between the onset of signs and symptoms suggestive of GCA and the definitive diagnosis (3±1 months) in the other patients of the cohort. Any difference was noted between the 2 groups, except fort the mean age at the onset, that seems earlier in GCA patients presenting with FUO. Conclusions: GCA patients presenting with constitutional symptoms may represents sometimes a diagnostic challenge; our results confirm that FUO must to be carefully investigated in elderly patients. Actually, there are major delays in the recognition of GCA patients presenting with FUO, and it partially seems to be due to the long diagnostic work-up before performing a rheumatologic evaluation. Disclosure of Interest: None Declared